Changes in the physical properties of an amazonian inceptisol induced by tractor traffic - Gomes, Romário Pimenta [UNESP]; Bergamin, Anderson Cristian; Silva, Laércio Santos [UNESP]; Campos, Milton César Costa; Cazetta, Jairo Osvaldo [UNESP]; Coelho, Anderson Prates [UNESP]; de Souza, Edicarlos Damacena (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2019)
With agricultural expansion in Amazonian regions, studies are needed to verify the effect of mechanization on the soils of the regions. This study aimed to assess soil physical attributes under different compaction conditions induced by tractor traffic on a soil of southern Amazonas State, Brazil. Treatments consisted of three compaction levels: conventional soil tillage without additional compaction (CT) and conventional soil tillage with additional compaction with four (CTc4) and eight tractor passes (CTc8). An intense increase in soil aggregate diameter was observed in the superficial soil layer (0.00-0.05 m) from four tractor passes, decreasing in the successive soil layers (0.05-0.20 m). Soil density increased up to a depth of 0.10 m. The reduced macroporosity and soil moisture on the soil surface (0.00-0.05 m) did not significantly alter soil microporosity in the different treatments. For the macroporosity, the 0.00-0.05 m layer was the most impaired, with a reduction of more than 50% for the treatments submitted to compaction (CTc4 and CTc8). The penetration resistance for the 0.00-0.05 m layer was increased by more than 150% between the treatment without compaction (CT = 0.88 MPa) and compaction (CTc4 = 2.25 MPa; CTc8 = 2.50 MPa). These results show a greater caution in the agricultural machinery management in Amazonian soils, which may be aggravated due to the intense water regime in the region.
Keywords: Compaction; Mechanization; Multivariate analysis; Physical attributes